Game-Based Al - Furqan Learning Strategies for Children at Tadika Didik Bistari Gemilang Gerik - Putri Nurul Aulia; Zailani (Bulletin of Science Education, 2024)
This research is based on the background that learning Al - Furqan (Al-Qur'an) in Tadika age children faces challenges in the form of low understanding and interest of children. Conventional methods that rely on reading and memorization are often less effective in attracting children's attention and maintaining their focus. This requires educators to develop learning approaches that are more engaging and appropriate to the child's developmental stage. Game-based learning strategies emerge as a potential solution to this problem. The type of research used in this study uses a qualitative approach with a qualitative descriptive method. The purpose is to explore information about Al-Furqan learning strategies at Tadika Didik Bistari Gemilang, Gerik Malaysia. The research subjects consisted of 4 educators, including 3 teachers and 1 institution owner. While the object of this research is Al-Furqan learning strategy in Tadika Didik Bistari Gemilang Gerik, Malaysia. As for collecting field data, researchers used observation, interview, and documentation techniques. The results of this study show that the strategies used in the whole series of teaching and learning activities in Al-Furqan consist of 2 strategies, namely interactive learning strategies and learning strategies while playing such as arranging hijaiyah letter cards to make it easier for children to remember and spell hijaiyah letters. In the teaching process, teachers carry out tasks related to the use of strategies, using techniques that consist of several aspects including learning strategy planning, application/implementation of learning strategies, and evaluation/reflection of learning strategies.